Protein status in phenylketonuria: A scoping review. Issue 4 (April 2022) - Firman, Sarah J.; Ramachandran, Radha; Whelan, Kevin; Witard, Oliver C.; O'Keeffe, Majella
Summary: Background & aims: The physical and functional outcomes of lifelong treatment with a phenylalanine restricted diet for the management of Phenylketonuria (PKU) remain unknown. Given that the mainstay of dietary management consists of modifying the sources of ingested protein, various aspects of body protein status could be compromised. Objectives: To examine the existing evidence regarding the protein status of people with PKU and identify nutritional and lifestyle variables that influence protein status. Eligibility criteria: Studies reporting anthropometric, biochemical and/or functional measurements of body protein status in people with PKU were eligible. Source of evidence: MEDLINE (Ovid), Embase (Ovid), CENTRAL, Web of Science and Scopus, and conference abstracts. Results: Seventy studies were included in the review. The majority of studies assessing protein status based on anthropometric measurements observed no differences between people with PKU and controls, although deficits in muscle mass were reported within PKU cohorts. Findings for biochemical assessment of protein status were mixed and limited studies assessed protein status using functional measures. Factors such as participant age, sex, metabolic control, protein source, type of protein substitute, and pharmacological treatments were found to modulate protein status of people with PKU. Conclusions: Findings were inconclusive regarding body protein status in people with PKU. The relationship between diet and protein status outcomes remains unclear and further research is warranted to determine the impact of dietary regimens on physical and functional outcomes, and to understand the best clinical assessments to reliably monitor the protein status in people with PKU.